Editorial Note (American Journal of Islam and Society, 1985)
When the first issue of the American Journal of Islamic Studies(AJIS) came out last spring, we announced that it was an organ of theAssociation of Muslim Social Scientists (AMSS) and that it is intended toserve as a forum for dialogue between Muslims in these United Statesand those elsewhere in the global Muslim community. We hope thenumber of articles published in the first and second issues of the journalhave served this purpose.In this third and fourth numbers of the journal we wish to announce achange of name. Why are we changing the name of the journal and whatis the new name? Well, the new name is the American Jouml of IslamicSocial Sciences (AISS). The decision to change the name of the journalwas made by the newly elected Executive Committee of the AMSS.Under the new President, Dr. Abdulhamid AbuSulaymanm, theExecutive feels that the term “Islamic Studies” does not necessarilyconvey the wider meaning and research objectives of the AMSS. It istrue that “Islamic Studies” encompasses a great deal in terms of studieson and about the Muslim World and peoples, but to further the cause ofthe AMSS and its members, the journal must begin to deal with thesocial science issues that bear on the Muslim World. This journal, theExecutive believes, could serve as the intellectual vehicle through whichthe Muslim identity and Muslim scholarship can not only benefit but alsodevelop along more authentic and less dependent lines. Of course some ofus in the Muslim World and within the ranks of the AMSS may arguethat the very name is presumptous. The point is well taken. Presently anIslamic social science is yet to develop but there is room for aspirations.The effort is certainly aspirational and the members of the AMSS andothers interested in Islamic affairs and in research about the Muslimsare called upon to give the idea a chance to develop.But actually, what is Islamic social science? This is a body ofknowledge that interprets scientifically acquired data along Islamiclines. It employs much of the tried and tested social science researchmethods to explain, analyse and discuss the human condition in Muslimsocieties; it formulates hypotheses and theories in the tradition of IbnKhaldun and Ibn Taymiyah and pursues knowledge to the farthestlimits set by the divinely created aql (human intellect). Onedistinguishing characteristics of an Islamic social science is the set ofmotives that propel the researcher. Rather than pursue knowledgesimply for the sake of knowledge, this approach to knowledge-acquiringand knowledge-processing places much emphasis on man’s role as ...